Audit Sistem Informasi Monitoring dan Evaluasi (Monev) Pada Puskesmas Kecamatan Ciracas Menggunakan COBIT 2019 - Dewi, Yumi Novita; Rindu Rifkawati Marbun (Fakultas Teknik Universitas Hamzanwadi, 2024)
This research starts from the framework of thinking that auditing information technology governance in monitoring and evaluation (monev) information systems using COBIT 2019 is an important thing to do. In the present and future, it is necessary to align information technology investments with the aim of community services in public health centers. The COBIT 2019 framework provides the benefits of implementing information systems, minimizing risks, and optimizing resources according to needs at the Ciracas District Health Center. In implementing monitoring and evaluation (monev), the factor design from COBIT 2019 can determine which domains must be assessed for their maturity level, so that agencies can know what needs to be improved. In this case, the EDM02 domain focuses on the process of optimizing the contribution of business value, services and IT assets resulting from investment at a cost that is acceptable to the company, while MEA03 ensures that the agency has complied with all applicable external requirements. Based on the results of the inspection, EDM02 has a current maturity value of 4.23 with a maturity level of 5-Optimized, which means that the implementation of monitoring and evaluation (monev) at the Ciracas District Health Center has run according to its objectives, while MEA03 has a current maturity value of 3.98 with a maturity level of 4- Manged and Measureable, which means monitoring and evaluation (monev) at the Ciracas District Health Center has been running well, even data or information has been integrated